Controlling Selectivity in Plasmonic Catalysis: Switching Reaction Pathway from Hydrogenation to Homocoupling Under Visible‐Light Irradiation. Issue 4 (14th December 2022) - Peiris, Erandi; Hanauer, Sébastien; Le, Tien; Wang, Jiale; Salavati‐fard, Taha; Brasseur, Paul; Formo, Eric V.; Wang, Bin; Camargo, Pedro H. C.
Abstract: Plasmonic catalysis enables the use of light to accelerate molecular transformations. Its application to the control reaction selectivity is highly attractive but remains challenging. Here, we have found that the plasmonic properties in AgPd nanoparticles allowed different reaction pathways for tunable product formation under visible‐light irradiation. By employing the hydrogenation of phenylacetylene as a model transformation, we demonstrate that visible‐light irradiation can be employed to steer the reaction pathway from hydrogenation to homocoupling. Our data showed that the decrease in the concentration of H species at the surface due to plasmon‐enhanced H2 desorption led to the control in selectivity. These results provide important insights into the understanding of reaction selectivity with light, paving the way for the application of plasmonic catalysis to the synthesis of 1, 3‐diynes, and bringing the vision of light‐driven transformations with target selectivity one step closer to reality. Abstract : Visible‐light irradiation was employed to accelerate and control reaction selectivity by harvesting plasmonic and catalytic effects in AgPd nanoparticles. By focusing on the hydrogenation of phenylacetylene, plasmonic effects allowed the control (switch) of the reaction pathway from hydrogenation (leading to ethylbenzene as the product in the dark) to homocoupling (leading to 1, 4‐diphenylbutadiyne as the product under visible‐light irradiation).